Numerical investigation of viscous flow through quasi-three dimensional multistage turbomachinery - Miao, Yi. (2009)
A good understanding of the computational fluid dynamics associated with rotor/stator configurations can be extremely useful when optimising the performance of turbomachinery. In this thesis, a quasi-three-dimensional, implicit, finite volume, time marching Navier-Stokes approach has been used to investigate the flow through three cases of the single stage in two subsonic turbines and a transonic compressor. Relative motion between the rotor and stator blades with arbitrary number of airfoils per row is made possible with the use of circumferentially averaging techniques on the inter-row mixing plane.